Trump presidency and US involvement in Middle East and the Muslim world - Ra'ees, Wahabuddin (2017)
President Trump when for running for the White House promised his supporters to make America Great again. He also instigated anti-Muslim feelings among his audience. He promised that he would move the US Embassy to Jerusalem. Finally, he made it to the White House and won the American Presidency. Analysis of his 100 days in office suggests that his presidency has been marred by the Russia scandal that he colluded with Putin’s Russia to win the presidency. Though Trump denies any Russian involvement in the US Presidential Election, investigation into Russia’s involvement and Trump’s team’s collaboration has begun to get to the truth. This has resulted in resignation of some of his top campaign advisers and officials. The development shows that Trump will have difficult time to deal with the Russia Inquiry and yet his administration will honor his election campaign agenda. Trump will revive the US active role in the Middle East and Syria. However, it is not sure if President Trump due to Russia Inquiry will survive to complete his term in office.